Penguatan Nilai-Nilai 1L5C dalam Pembelajaran Sejarah di SMA Kolese De Britto Yogyakarta di Masa Pandemi - Merdilince Sitorus; Rhoma Dwi Aria Yuliantri; Asyif Awaludin Romadhoni (Universitas Negeri Padang, 2023)
This research aims at examining: (1) the 1L5C values in History learning; and (3) the IL5C characters values reinforcement in History learning at SMA Kolese De Britto, Yogyakarta. This research is a descriptive-qualitative research utilizing Miles and Huberman’s analysis model. The data in this research were collected using observation, interviews, and document study techniques. In addition, data triangulation was employed to validate the data. The findings of this research are: (1) The 1L5C characters values have been implemented in History learning, so it influences the reinforcement of the values for the students. The interviews and document analyses show that the History teacher has integrated the 1L5C characters values through History learning, which has been included into the Syllabus, Learning Plan, and learning materials. (3) The reinforcement of 1L5C characters values were realized through learning process which include preparing learning devices, developing History materials through discussion, presentation, and independent assignment. The reinforcement of 1L5C characters values have been designed and programmed by the school through various methods including spiritual activities, talent-group De Britto Morning Assembly, live-in tolerance, and professional orientation. The activities to internalize 1L5C in the 11th Grade of SMA Kolese De Britto Yogyakarta are in line with 2013 Curriculum.